Self-Efficacy Beliefs of University Students: Examining Factor Validity and Measurement Invariance of the New Academic Self-Efficacy Scale - Greco, Andrea; Annovazzi, Chiara; Palena, Nicola; Camussi, Elisabetta; Rossi, Germano; Steca, Patrizia (Frontiers in Psychology, 2022)
Academic self-efficacy beliefs influence students’ academic and career choices, as well as motivational factors and learning strategies promoting effective academic success. Nevertheless, few studies have focused on the academic self-efficacy of university students in comparison to students at other levels. Furthermore, extant measures present several limitations. The first aim of this study was to develop a reliable and valid scale assessing university students’ self-efficacy beliefs in managing academic tasks. The second aim was to investigate differences in academic self-efficacy due to gender, years of enrollment, and student status. The study involved 831 students (age M = 21.09 years; SD = 1.34 years; 66.3% women) enrolled in undergraduate programs. Indicators of academic experiences and performance (i.e., number of exams passed and average exam rating) were collected. A new scale measuring students’ academic self-efficacy beliefs was administered. Results from a preliminary Exploratory Factor Analysis were consistently supported by findings from a Confirmatory Factor Analysis. Multigroup CFA supported the presence of measurement invariance. Analyses revealed that the new scale has eight factors: “Planning Academic Activities,” “Learning Strategies,” “Information Retrieval,” “Working in Groups,” “Management of Relationships with Teachers,” “Managing Lessons,” “Stress Management,” and “Thesis Work.” Self-efficacy dimensions showed significant relations with academic experiences and students’ performance indicators, as well as differences due to gender, years of enrollment, and student status. Findings are discussed in terms of practical implications for the implementation of intervention programs aimed at fostering self-efficacy beliefs and academic success.